How Orthodontıc Facebow Injurıes Occur: Selectıng Effectıve Safety Devıces To Avoıd Them - Russell H.A. Samuels; Gerhard Michael Doll (Galenos Yayinevi, 1998)
Reports of injuries from orthodontic facebows have occasionally appeared in the Dental and medical literature. These reports are rare but the injuries can be disastrous and Clinicians must know how to avoid them. How these injuries occur is described. The effectiveness of the currently available safety devices in preventing these injuries is discussed. It is concluded that the facebow needs to be prevented from coming out of the extra oral traction tubes during use. It is suggested that a locking orthodontic facebow and a self releasing extra oral traction system are used as the most effective combination of safety devices.